Implementasi Fatwa Dsn-Mui Nomor 88/Dsn-Mui/Xi/2013 Dalam Penyelenggaraan Dplk Di Bank Muamalat Pekalongan - Pertiwi, Nabilla Priyant; Wahid, Soleh Hasan; Sofiani, Trianah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to describe the mechanism for administering Financial Institution Pension Funds at Bank Muamalat Pekalongan and analyze the compliance of its management with Fatwa MUI No. 88/DSN-MUI/XI/2013. This research employs an empirical juridical method with a qualitative approach to gain an in-depth understanding of the implementation of sharia principles in pension fund management at Bank Muamalat Pekalongan. The findings indicate that Bank Muamalat Pekalongan has implemented the Financial Institution Pension Fund (DPLK) program in accordance with the regulations set forth in Fatwa DSN-MUI No. 88/DSN-MUI/XI/2013 general guidelines for implementing pension programs based on sharia principles , covering fund collection from participants, investment management following sharia principles, and pension benefit distribution to eligible participants. Bank Muamalat also applies the DPLK mechanism in compliance with Fatwa DSN-MUI provisions, including the use of sharia contracts such as Wakalah Bil Ujrah in fund management. Additionally, investments are made solely in halal financial instruments and are supervised by the Sharia Supervisory Board (DPS) to ensure adherence to sharia principles.